SLA information management through dependency digraphs: The case of cloud data services - Stamou, Katerina; Kantere, Verena M.; Morin, Jean Henry; Georgiou, Michael (My University, 2014)
The paper addresses the issue of Service Level Agreement (SLA) data management for the cloud computing domain. We discuss the SLA anatomy and provide an analysis of SLA data management requirements. The analysis highlights SLA data aspects considering the association of SLA terms with service management operations. Our work proposes a simple, structured way to store and manage SLA information through a digraph data model that is modular, extensible and expressive with respect to data operational dependencies. The proposed SLA digraph considers properties of SLA terms and service component dependencies. We sketch a realistic dataservice provisioning scenario, where the proposed SLA digraph is applied. We illustrate the mapping of data service attributes into SLA terms and the role of edge properties in the definition of service dependencies.
Keywords: Directed graphs; Microcellular radio systems; Systems science; Cloud data